Multiancestry association study identifies new asthma risk loci that colocalize with immune-cell enhancer marks. (January 2018) - Demenais, Florence; Margaritte-Jeannin, Patricia; Barnes, Kathleen; Cookson, William; Altmüller, Janine; Ang, Wei; Barr, R.; Beaty, Terri; Becker, Allan; Beilby, John; Bisgaard, Hans; Bjornsdottir, Unnur; et al.
Abstract We examined common variation in asthma risk by conducting a meta-analysis of worldwide asthma genome-wide association studies (23, 948 asthma cases, 118, 538 controls) of individuals from ethnically diverse populations. We identified five new asthma loci, found two new associations at two known asthma loci, established asthma associations at two loci previously implicated in the comorbidity of asthma plus hay fever, and confirmed nine known loci. Investigation of pleiotropy showed large overlaps in genetic variants with autoimmune and inflammatory diseases. The enrichment in enhancer marks at asthma risk loci, especially in immune cells, suggested a major role of these loci in the regulation of immunologically related mechanisms. The authors perform meta-analysis of GWAS studies for asthma from multiancestral cohorts. They identify five new loci and find that the asthma-associated loci are enriched near enhancer marks in immune cells.